2022
DOI: 10.1210/endocr/bqac104
|View full text |Cite
|
Sign up to set email alerts
|

N/C Interactions Are Dispensable for Normal In Vivo Functioning of the Androgen Receptor in Male Mice

Abstract: The androgen receptor (AR) plays a central role in the development and maintenance of the male phenotype. The binding of androgens to the receptor induces interactions between the carboxyterminal ligand-binding domain and the highly conserved 23FQNLF 27 motif in the amino-terminal domain. The role of these so-called N/C interactions in AR functioning is debated. In vitro assays show that mutating the AR in the 23FQNLF 27 motif (called AR NoC) attenuates the AR transactivation of reporter genes, has no effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Surprisingly, this did not affect the AR function in a mutant mouse model. This finding challenges the in vivo role of this AR-specific dimerization mode but does not exclude its role in prostate cancer [ 50 ]. In contrast, disrupting the LBD dimerization of the AR by a point mutation in the mouse genome leads to androgen insensitivity in the absence of accessory sex glands despite much higher circulating testosterone levels.…”
Section: Session 2: New Advances From Basic and Translational Researchmentioning
confidence: 99%
“…Surprisingly, this did not affect the AR function in a mutant mouse model. This finding challenges the in vivo role of this AR-specific dimerization mode but does not exclude its role in prostate cancer [ 50 ]. In contrast, disrupting the LBD dimerization of the AR by a point mutation in the mouse genome leads to androgen insensitivity in the absence of accessory sex glands despite much higher circulating testosterone levels.…”
Section: Session 2: New Advances From Basic and Translational Researchmentioning
confidence: 99%
“…62,63 In vitro studies have also suggested critical interactions between the N-terminus and C-terminus in AR transactivation, although more contemporary in vivo work suggests that this property may be dispensible. 64 In recent years, various constitutively active AR-Vs have been characterized that lack the LBD and may command AR programs in a ligand-independent manner. [65][66][67][68] Importantly, the majority of current AR-directed agents either directly interact with or require a functioning LBD and thus do not act on AR-Vs.…”
Section: Ar Structure/functionmentioning
confidence: 99%
“…Ligand binding induces: 1) dissociation of AR from the HSP complex; 2) conformational changes including an N-to-C intramolecular interaction; and 3) activation of its nuclear localization signal followed by AR import into the nucleus (28,29). It is of note that the physiological function of AR N/C interactions are debated, as a recent paper showed reduced in vitro transactivation capacity by an AR mutant lacking N/C interactions in luciferase reporters, while no effect on male development was observed in mice bearing the same mutation (30). In the nucleus, AR interacts with its nuclear cofactors via its AF-1 and AF-2 (31,32) and both functions are suggested to have specificity for coregulator subsets, with the AF-1 being sufficient to drive AR target gene expression in the absence of AF-2.…”
Section: Ar Biology: the Basicsmentioning
confidence: 99%